Psychological inflexibility and intolerance of uncertainty moderate the relationship between social isolation and mental health outcomes during COVID-19 - Smith, Brooke M. (J Contextual Behav Sci, 2020)
The COVID-19 pandemic has had an enormous impact on human activity worldwide, in part due to many governments issuing stay-at-home orders and limiting the types of social interactions in which citizens can engage. Previous research has shown that social isolation can contribute to psychological distress. The impact of increased social isolation on mental health functioning during the COVID-19 crisis, as well as potential mechanisms to buffer this impact, have yet to be investigated. The current study explored the moderating role of psychological flexibility and related constructs on the relationships between social isolation and mental health outcomes during the COVID-19 pandemic. Cross-sectional data from 278 participants, the majority residing in the United States, were collected during a 3-week period from mid-April to early May 2020 via online survey. A series of hierarchical linear regression analyses indicated statistically significant relationships between social isolation and psychological distress (depression, anxiety, and stress), well-being, and valued living. Psychological inflexibility, intolerance of uncertainty, and emotional suppression significantly moderated these relationships in a number of instances. Greater psychological flexibility and acceptance of difficult experiences appeared to act as a buffer against the negative effects of increased social isolation, while amplifying the benefits of social connectedness. Implications for promoting mental health and buffering against the harmful effects of social isolation during the COVID-19 pandemic and beyond are discussed.